A study of sheath blight disease on paddy in the northern region of Peninsular Malaysia / Nur Solehah Razman - Razman, Nur Solehah (Faculty of Plantation and Agrotechnology, 2017)
Sheath blight (Rhizoctonia solani) disease is the one of the most serious disease that affects the rice production in northern Malaysia. At present, the sheath blight has widely established in many areas cultivation rice in Malaysia and reported to result in a revenue loss of about 50% with severe attacks. Sheath blight disease has managed to infect a variety of new as well, MR219. It will spread rapidly during flowering to seed filling stage, especially when conditions are favourable. A study was conducted to study the details of the current state of sheath blight disease and the extent of damage caused by the disease. Currently, there is no information is carry out of the sheath blight disease in the northern region of peninsular. The present study was carried out in order to determine the incidence and severity of rice sheath blight disease and was to determine the factors that contributing to the sheath blight disease incidence and severity in several different granary area at Seberang Perak, Kedah and Penang. It is important to collect and record data sheath blight disease bacteria for further analysis. Data collected were disease severity and incidence of the sheath blight. The results were observed different granary area which located at Felcra Seberang Perak, Kampung Guar Kepayang, Penang and Kampung Bonggol Berangan, Kedah. The highest mean of disease incidence was recorded in Kedah which was 55.27% and the lowest was recorded in Penang which was 50.46%. Furthermore, the highest disease severity was recorded in Perak which was 56.59% and the lowest disease severity was recorded in Penang which was 43.7%. The sheath blight pathogen was isolated on PDA medium.The result for hyphae observation was be done by using the microscope. The Koch’s postulates method has proven that the pathogen of the sheath blight was Rhizoctonia solani. Generally, all incidence and severity in northern was at high levels and unsafe. Morphological observation presented that isolated pathogen have the similar characteristics to the publish Rhizoctonia solani.